The efficacy of interventions to increase physical activity participation of children with cerebral palsy: A systematic review and meta-analysis - Reedman, S.; Boyd, Roslyn; Sakzewski, L. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Mac Keith Press.Aim: To determine efficacy of therapy and behaviour change interventions to increase the level of participation in leisure-time physical activities (LTPAs) and habitual physical activity in children and young people with cerebral palsy. Method: Five databases were systematically searched. Included studies were randomized or comparison designs. Methodological quality was assessed with a modified Downs and Black Scale. Quantitative analysis was performed using RevMan 5.3 (The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen, Denmark). Intervention components and behaviour change constructs were mapped against (1) the International Classification of Functioning, Disability and Health (ICF) and (2) the Theoretical Domains Framework. Results: Searches yielded 2487 unique articles. Eight studies (nine articles) were included. Interventions included physical training, activity level training, combined physical training and behaviour change therapy, online behaviour change modules, and context-focused therapy. Study quality varied from moderate to high. There was a small, significant effect of physical activity intervention compared with passive usual care on level of habitual physical activity, of approximately 1000 additional steps per day (standardized mean difference 0.34, 95% confidence interval 0.03-0.66, p=0.030). There was no significant effect on LTPA participation (standardized mean difference 0.40, 95% confidence interval -0.40 to 1.19, p=0.330). Interpretation: Therapy and behaviour change interventions have the potential to increase LTPA participation of children and young people with cerebral palsy, although there is a need to depart from impairment-focused approaches. Inappropriate selection of outcomes and inadequate reporting of complex interventions are barriers to progress in this field.